2017
DOI: 10.3390/ijms18050960
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Mechanism of Quorum-Sensing in Enterococcus faecalis: Its Role in Virulence and Therapeutic Approaches

Abstract: Quorum-sensing systems control major virulence determinants in Enterococcus faecalis, which causes nosocomial infections. The E. faecalis quorum-sensing systems include several virulence factors that are regulated by the cytolysin operon, which encodes the cytolysin toxin. In addition, the E. faecalis Fsr regulator system controls the expression of gelatinase, serine protease, and enterocin O16. The cytolysin and Fsr virulence factor systems are linked to enterococcal diseases that affect the health of humans … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
91
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(93 citation statements)
references
References 120 publications
0
91
0
2
Order By: Relevance
“…The virulence factors that we have detected include proteinases, gelatinases, and hyaluronidases that have extensively been described in previous studies, [59][60][61] as well as virulence regulators, such as fsrABC and bopD, that seem to play an important role in pathogenesis. 62,63 With regard to AMR genes, we have identified several that are chromosomally located and nontransferable, and associated with resistance to trimethoprim (dfrE), fluoroquinolones (emeA and efrAB), and clindamycin (lsaA) in E. faecalis. 64,65 However, the enterococci isolates were sensitive to nearly all the antibiotics tested in our study, including β-lactams chloramphenicol, vancomycin, erythromycin, and tetracycline.…”
Section: Discussionmentioning
confidence: 99%
“…The virulence factors that we have detected include proteinases, gelatinases, and hyaluronidases that have extensively been described in previous studies, [59][60][61] as well as virulence regulators, such as fsrABC and bopD, that seem to play an important role in pathogenesis. 62,63 With regard to AMR genes, we have identified several that are chromosomally located and nontransferable, and associated with resistance to trimethoprim (dfrE), fluoroquinolones (emeA and efrAB), and clindamycin (lsaA) in E. faecalis. 64,65 However, the enterococci isolates were sensitive to nearly all the antibiotics tested in our study, including β-lactams chloramphenicol, vancomycin, erythromycin, and tetracycline.…”
Section: Discussionmentioning
confidence: 99%
“…We have detected gelE ‐ sprE in highest percentages, but the decrease in frequencies observed for fsrAB and fsrC locus, respectively (Table ). Mutated fsrABC affects the downstream transcriptional response of gelE , sprE , ef1097 and ef1097b and its deletion completely abolished the expressions of gelE and sprE (Ali, Goraya, et al, ). Despite this fact, the poultry and one clinical isolate devoid of fsr operon rendered unaffected for protein hydrolysis (Tables and ), suggested that the sequence divergence at priming sites might result in the failure of amplification without affecting the expression of proteases.…”
Section: Discussionmentioning
confidence: 99%
“…Despite this fact, the poultry and one clinical isolate devoid of fsr operon rendered unaffected for protein hydrolysis (Tables and ), suggested that the sequence divergence at priming sites might result in the failure of amplification without affecting the expression of proteases. Interestingly, ef1097 locus located 800 kb upstream of the fsr operon promotes antimicrobial activities by encoding a pre‐proprotein EntV , further modified by gelE (Ali, Goraya, et al, ). In current findings, ent1097 and gelE were the congruent genotypes; however, ef1097 not detected in gelE ‐positive isolates might be the consequence of mutation at 800 kb upstream of the fsr operon (Table ).…”
Section: Discussionmentioning
confidence: 99%
“…Enterococcus faecalis has emerged as a significant cause of nosocomial infections in the last two decades, resulting in urinary tract infections, bacteremia, prosthetic joint infection, abdominal-pelvic infections, and endocarditis [1]. E. faecalis has resistance to many commonly used antimicrobial agents, and vancomycin-resistant enterococci (VRE) has emerged as a major cause of nosocomial infection outbreaks in recent years [2].…”
Section: Introductionmentioning
confidence: 99%